Penerapan Metode Haversine Formula Pada Aplikasi Pencarian Lokasi Tempat Tambal Ban Kendaraan Bermotor Berbasis Mobile Android - Ahmad Fauzi; Frengky Pernando; Mugi Raharjo (Universitas Bina Sarana Informatika, 2018)
In essence, quoted from a survey conducted by Jakarta Transportation Statistics Jakarta - BPS Jakarta explains that motor vehicle users in DKI Jakarta area in 2014 as much as 13,084,372 with annual growth of 10, 54% and added with passenger car, load car, car bus and rensusu of 17,523,967 with a lot of numbers will certainly cause many problems between the defects and the most feared is the leakage of the vehicle tire probadi, to facilitate the private motorists in finding a place tire feeding is necessary application of vehicle tire repair information so the riders do not have to walk far to find a place of tire repair whereas the possibility of rider position is not too far away with the location they are looking for, the application will find the closest distance from where the tire patch that has been registered by the seller of the service.